Ocular Complications after Intravitreal Bevacizumab Injection in Eyes with Choroidal and Retinal Neovascularization - Hanfi, Umair Qidwai, Aimal Khan, P.S Mahar, Azfar Nafees (Pakistan Journal of Ophthalmology, 2010)
Purpose: To assess the ocular complications after intra-vitreal Bevacizumab (Avastin) injection in eyes with choroidal and retinal neovascularization. Materials and Method: This study was conducted in Isra Post-graduate Institute of Ophthalmology, Al-Ibrahim Eye Hospital, Karachi. The patients were selected through simple random sampling. This was a quasi experimental study. It was conducted from 21.07.2007 to 20.07.2008. All the 200 patients with neovascularization who fulfilled the inclusion criteria, were selected on outpatient basis and were treated with intravitreal bevacizumab on day care basis. They were re-examined the next day and evaluated for complications. Data was collected according to proforma and analysis was done using SPSS version 17.0. Results: Study was conducted on 200 patients with choroidal and retinal neovascularization. Average age of patients was 53.7 with (±SD =11.7) years (Range = 25 – 83 years). The most common indication of intravitreal bevacizumab was diabetic retinopathy found in 110 (55%) patients. Complications were seen only in 24 (12%) patients. Sub Conjunctival hemorrhage was the most common but least serious complication found in 12 (50%) patients, followed by Corneal Abrasion in 4 (16.7%), while raised IOP, Vitreous Hemorrhage, Transient mild uveitis and lens Injury was seen in only 2 (1%) patients. Conclusion: Adverse effects of intravitreal Bevacizumab are mostly procedure related but few may be drug related. The procedure is generally safe but there are risks involved. To minimize the risk careful attention to injection technique and appropriate post injection monitoring are essential. The short term results suggest that intravitreal Bevacizumab is safe procedure.